A micromobility buffet: e-scooters in the context of multimodal spaces and practices in Greater Manchester. Issue 1 (2023) - Sherriff, Graeme; Lomas, Michael J.; Blazejewski, Luke; Larrington-Spencer, Harriet
No abstract available